2010
DOI: 10.1007/s10567-010-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

The Metacognitive Model of Generalized Anxiety Disorder in Children and Adolescents

Abstract: Worry is a common phenomenon in children and adolescents, with some experiencing excessive worries that cause significant distress and interference. The metacognitive model of generalized anxiety disorder (Wells 1995, 2009) was developed to explain cognitive processes associated with pathological worry in adults, particularly the role of positive and negative beliefs about worry. This review evaluates the application of the model in understanding child and adolescent worry. Other key issues reviewed include th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 62 publications
6
49
0
3
Order By: Relevance
“…In addition, a group of researchers revealed that there is a significant relationship between biased attention and negative thought in one hand and early maladaptive schemas in the other hand. In the present study, the students with social phobia got a lower score comparing the student with no psy- (29)(30)(31). They have mentioned that metacognitive aspects such as positive beliefs about worriedness and low cognitive trust can be the causative agents of social phobia.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, a group of researchers revealed that there is a significant relationship between biased attention and negative thought in one hand and early maladaptive schemas in the other hand. In the present study, the students with social phobia got a lower score comparing the student with no psy- (29)(30)(31). They have mentioned that metacognitive aspects such as positive beliefs about worriedness and low cognitive trust can be the causative agents of social phobia.…”
Section: Discussionmentioning
confidence: 48%
“…This argument is not new-others have argued for control beliefs as a key factor in the development of anxiety (Chorpita & Barlow, 1998). Indeed, metacognitive accounts of pathological worry suggest that beliefs about the negative consequences of worry (including the belief that worry is uncontrollable, e.g., "it is impossible to stop myself from worrying") are associated with greater worry and anxiety (Ellis & Hudson, 2010). However, that control beliefs played such a key role in the context of other important anxiety-related risk factors warrants particular attention.…”
Section: Discussionmentioning
confidence: 99%
“…This included the belief that worry both helps to solve problems and avoid the worst. There is mixed evidence for the hypothesis that positive beliefs about worry are normal in young people with and without pathological worry (Ellis & Hudson, 2010). Wells (1995Wells ( , 2009 suggested that activation of negative beliefs about the uncontrollability and danger of worry would uniquely contribute to the development and maintenance of pathological worry in anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bacow et al (2009) reported that there were no significant differences between clinically anxious and non-clinical participants with regard to negative beliefs about worry. It is only through ongoing research that our understanding of worry can be further advanced in child and adolescent populations (Ellis & Hudson, 2010).…”
Section: Introductionmentioning
confidence: 99%